Теоретико-концептуальное моделирование в маркетинговом исследовании: системно-методологические аспекты - Резник, В. (Социология: теория, методы, маркетинг, 1999)
Within the frames of marketing research, there are presented some aspects of how the empirical indicators, related to individual customer’s behavior, can be theoretically interpreted. Basing on system approach, the author studies theoretical concept models of the research object and subject. The main functions of the models are defined.